Arabic Educational Courseware (E-ArabiC) / Noor Aina Farhana Zainudin - Zainudin, Noor Aina Farhana (2014)
Arabic Language is one of third languages offered to UiTM (Terengganu) students which are also a compulsory subject in their courses. Arabic Educational Courseware (E-ArabiC) has been developed for helping UiTM student in learning Arabic Level II in UiTM (Terengganu). This is because currently Arabic Level II does not provide any application tools for this subject. Besides, the students also are taught using traditional method, complement by Arabic Languages textbook in order to practice properly pronunciation and grammar of this subject. This courseware is design based on ADDIE Model in order to provide a guideline in development of courseware that would fulfill the needs in teaching and learning process. ADDIE Model is one of the instructional system design model (ISD). By using interactive multimedia, this courseware can help in improving students’ competence in learning and practicing Arabic Languages. An interview was conducted with the expertise and questionnaires were distributed to the students to get feedback on this project.The results of the evaluation indicated that usability construct shows the highest mean, Mean=4.61 and SD=0.558 between others construct. It shows students are very interested in using courseware as part of their learning process because E-ArabiC is effective and ease to use. The courseware needs further enhancement in terms of contents, examples given and exploitation of multimedia elements to serve as a complete learning and teaching aid in near future.